Lean production principles in construction projects design and delivery - Struková, Z. (Видавництво Львівської політехніки, 2011)
Whereas lean principles are not only manufactury oriented, they are of use in a special industry like construction is, lean thinking can be considered as a manner to manage construction. The paper deals with the lean production application in construction projects design and delivery.
Принципи раціонального виробництва при розробці і реалізації будівництва
Keywords: lean construction; lean production; construction design; integrated project delivery; collaboration